Propuesta de una campaña de comunicación institucional y relaciones públicas para socializar el proyecto Desnutrición Cero dirigido a mujeres embarazadas y con niños de hasta un año de edad, de las parroquias rurales de la provincia de Pichincha Nayón, Zámbiza y Tumbaco entre los años 2011 y 2013, que lleva a cabo el Ministerio de Salud Pública del Ecuador - Salazar Murillo, María Catalina (2012)
The purpose of the following study is to establish strategies for a Corporate Communication and Public Relation Campaign, so that the project Desnutrición Cero, proposed by the Ministerio de Salud Pública del Ecuador, could be socialize, in order to obtain the involvement of the target group. According to the World Food Program, Ecuador is the fourth country of Latin America, which has the highest child malnutrition rate, percentage. Considering this situation, four Ministries are launching a plan called Acción Nutrición. As part of this action, the Ministerio de Salud Pública has developed the project Desnutrición Cero. Since, this project is focus on the care of pregnant women and newborns until they turn one year old. However, this project has a lack of dissemination and the little work that has been done is not totally supported. With this background, it is important to conduct a field investigation to determine the characteristics, needs and expectations of the target group, so that the project Desnutrición Cero can be socialized in rural parishes of the Province of Pichincha. In this case it will be considered recommend to start with the parishes of Nayón, Zámbiza and Tumbaco, because their population requires this type of attention.